Magnetic Core–Shell to Yolk–Shell Structures in Palladium‐Catalyzed Suzuki–Miyaura Reactions: Heterogeneous versus Homogeneous Nature. Issue 6 (27th May 2016) - Li, Yinle; Zhang, Zhuqing; Fan, Tao; Li, Xiaoguang; Ji, Jin; Dong, Pei; Baines, Robert; Shen, Jianfeng; Ye, Mingxin
Abstract: This study describes a comparative investigation on the heterogeneous versus homogeneous nature of the Pd‐catalyzed Suzuki–Miyaura cross‐coupling reaction mechanism with specific magnetic hierarchical core–shell and yolk–shell structures. The hierarchical core–shell Fe3 O4 @SiO2 ‐Pd@ m CeO2 ( m =mesoporous) catalyst contains a core of nonporous silica‐sheltered magnetite (Fe3 O4 ) nanoparticles (NPs), a transition layer of active palladium (Pd) NPs, and an outer shell of porous ceria (CeO2 ). The magnetic yolk–shell Fe3 O4 @ h ‐Pd@ m CeO2 ( h =hollow) catalyst was prepared by selectively etching the nonporous silica interlayers. Notably, the results of the hot‐filtration heterogeneity test, the effect of Pd concentration, and solid‐phase poisoning, indicate that the two kinds of catalysts function in Pd‐catalyzed Suzuki–Miyaura cross‐coupling reactions through different catalytic mechanisms. Moreover, both catalysts demonstrated better catalytic activity than the Fe3 O4 @SiO2 ‐Pd catalyst. This finding can be ascribed to the outermost CeO2 shell having a high concentration of trivalent cerium and oxygen vacancies, which gives rise to the increased electron density of Pd NPs, and a faster rate‐determining step in the oxidative addition reaction for the Suzuki reaction. In addition, we propose a feasible mechanism elucidating the synergistic effect between the supporting CeO2 and active species. Abstract : Delving deeper : Two different catalysts having magnetic hierarchical core–shell and yolk–shell structures (see figure) are compared in terms of their reaction mechanisms for the Pd‐catalyzed Suzuki–Miyaura cross‐coupling reaction mechanism.